2019
DOI: 10.4085/1062-6050-581-18
|View full text |Cite
|
Sign up to set email alerts
|

Exertional Heat-Stroke Preparedness in High School Football by Region and State Mandate Presence

Abstract: Context Exertional heat stroke (EHS) is a leading cause of sudden death in high school football players. Preparedness strategies can mitigate EHS incidence and severity. Objective To examine EHS preparedness among high school football programs and its association with regional and state preseason heat-acclimatization mandates. Design Cross-sectional study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…When state officials and athletics administrators are considering their ability to affect high school student athlete health and safety, we would strongly encourage a state requirement for a heat modification policy that takes into account geographical meteorological conditions, work-to-rest ratios, types, timing and length of physical activity, and protective equipment considerations. Such a requirement appears to have a strong effect on both policy adoption and patient outcomes, as suggested in our results and previous research [ 12 , 18 , 25 , 26 , 27 , 31 ]. These results are paralleled by previous discoveries of Kerr et al [ 18 ], who found that when states required heat acclimatization policies, high schools were more likely to be fully compliant with the NATA Inter-Association Task Force guidelines on heat acclimatization in states that mandated the guidelines.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…When state officials and athletics administrators are considering their ability to affect high school student athlete health and safety, we would strongly encourage a state requirement for a heat modification policy that takes into account geographical meteorological conditions, work-to-rest ratios, types, timing and length of physical activity, and protective equipment considerations. Such a requirement appears to have a strong effect on both policy adoption and patient outcomes, as suggested in our results and previous research [ 12 , 18 , 25 , 26 , 27 , 31 ]. These results are paralleled by previous discoveries of Kerr et al [ 18 ], who found that when states required heat acclimatization policies, high schools were more likely to be fully compliant with the NATA Inter-Association Task Force guidelines on heat acclimatization in states that mandated the guidelines.…”
Section: Discussionsupporting
confidence: 85%
“…In the US, each state can set forth its own set of policy requirements for local high schools to follow. State policies have been shown to be effective at reducing EHS risk and has been identified as a facilitator for local emergency policy adoption [ 12 , 25 , 26 , 27 ]. Despite this, Adams et al [ 28 , 29 ] found that very few states require their high school athletics programs to follow best practice recommendations with regards the prevention and treatment of EHS.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research supports this assumption by showing that the implementation of policies at the state level has been effective at reducing exertional heat illness rates 4,27 and has also shown success with improving high school adoption of the policies. [28][29][30] Yet, the lack of policy compliance would of course increase vulnerability and local implementation of a policy stronger than the statewide mandate would be protective. Finally, Orr and Inoue 11 point out that the CVSO framework is new and untested.…”
Section: Discussionmentioning
confidence: 99%
“…This information has been widely shared for the past 20 years in NATA sponsored consensus statement, position statements, and education competencies. Yet, recent evidence by Kerr et al (2019) has shown that approximately 50% of ATs working at the high school level recently reported not using CWI to treat EHS. In 2011, the educational competencies for ATs were updated to include the addition of various acute care skills to help stabilize a patient before emergency medical services transport an athlete (Commission on Accreditation of Athletic Training Education, 2011).…”
Section: Preceptors and Professionals Staying Up To Date With Current Best Practicesmentioning
confidence: 99%